New Properties of BK-Spaces Defined by Using Regular Matrix of Fibonacci Numbers - Ercan, Sinan; Bektas, Cigdem A. (Amer Inst Physics, 2016)
In the present paper, we studied the new properties of BK-spaces which were defined using regular matrix of Fibonacci numbers in [1]. We computed alpha-, beta-, gamma- duals of these spaces and obtained Schauder basis. We also derived some topological properties of these spaces.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE
Keywords: Sequence-Spaces; Transformations